2015
DOI: 10.1177/1362168815606161
|View full text |Cite
|
Sign up to set email alerts
|

Similar prompts may not be similar in the performance they elicit: Examining fluency, complexity, accuracy, and lexis in narratives from five picture prompts

Abstract: Only a few characteristics of picture-based narrative prompts have been studied to determine what features affect task performance. Thus, it is not easy to identify equivalent narrative prompts or identify features that are impactful. Tavakoli and Foster (2008) and Tavakoli (2009) examined the impact of prompt on the language produced by English learners during a picture-based narrative task in respect to narrative structure and storyline complexity. This study investigates if prompts within these known catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…4 Notably, it has been shown that L2 learners' speech (fluency in particular) is susceptible to change, when they repeat the same speaking task immediately (e.g., Lambert, Kormos, & Minn, 2018). Our pilot data showed that using different story telling tasks resulted in different speaking behaviours within the same speaker (especially in terms of pronunciation) (see also De Jong & Vercellotti, 2016). We call for future studies which will probe the complex relationship between different types of The length of the speech samples in the current study was substantially longer (M = 142 sec ranging from 95 to 301 sec) than our precursor research (Saito & Akiyama, 2017), which used relatively short speech samples elicited via picture descriptions (M = 30 seconds, 40 words), and thus the current study included a sufficient number of words for robust lexical analyses (M = 105.3 words ranging from 55 to 206 words).…”
Section: Pre-/post-test Materialsmentioning
confidence: 79%
“…4 Notably, it has been shown that L2 learners' speech (fluency in particular) is susceptible to change, when they repeat the same speaking task immediately (e.g., Lambert, Kormos, & Minn, 2018). Our pilot data showed that using different story telling tasks resulted in different speaking behaviours within the same speaker (especially in terms of pronunciation) (see also De Jong & Vercellotti, 2016). We call for future studies which will probe the complex relationship between different types of The length of the speech samples in the current study was substantially longer (M = 142 sec ranging from 95 to 301 sec) than our precursor research (Saito & Akiyama, 2017), which used relatively short speech samples elicited via picture descriptions (M = 30 seconds, 40 words), and thus the current study included a sufficient number of words for robust lexical analyses (M = 105.3 words ranging from 55 to 206 words).…”
Section: Pre-/post-test Materialsmentioning
confidence: 79%
“…If the task-essential vocabulary was quite different in four writing tasks, this might indicate a task effect and could explain some of the differences in the effect of feedback on both revision and accuracy of new texts. In a recent study de Jong and Vercellotti (2016) found that speaking performance varied with prompts that were similar in narrative structure, storyline complexity, and number of elements. Since in the present study feedback targeted a broad range of linguistic features, it might also have caused cognitive overload for some learners and interrupted their feedback processing (Van Beuningen, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…The findings of this study were further employed as validation of the way TC was operationalised through two levels of IR demands and the way each task was selected and incorporated as a stimulus of speech production. The current study thus responded to the calls for researchers to validate their TC manipulation and prompts selection (De Jong & Vercellotti, 2016). Attempting to offer a more systematic operationalisation of TC variables, the present study proposed a two-level operationalisation of IR at the levels of task instructions and task content (for further detail, see Awwad et al, 2017, andTavakoli, 2019).…”
Section: Discussionmentioning
confidence: 88%
“…The silent nature of the episodes makes them appropriate tasks to operationalise IR in which the learners can reason the characters' intentions, read their thoughts, predict their actions, and justify their decisions. De Jong and Vercellotti's (2016) framework of prompts selection…”
Section: Tasks and Materialsmentioning
confidence: 99%
See 1 more Smart Citation